THE IMPORTANCE OF TECHNICAL EDUCATION IN MADRASSAS: EMPOWERING SCHOLARS FOR LIVELIHOOD AND COMMUNITY DEVELOPMENT IN PAKISTAN - Abdul Waheed Tariq; Allah Ditta; Dr. Muhammad Fakhar ud din; Dr. Sheraz Ahmad; Imran Khan; Shohab Khan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
The article explores the importance of technical education in madrassas in Pakistan, highlighting the need for a balanced education that includes both Islamic and technical knowledge. While learning Islamic knowledge is mandatory for scholars to become better Muslims and serve their communities, technical education can equip them with the necessary skills to secure livelihoods and contribute to community development. The article presents the challenges faced by madrassa graduates in finding meaningful employment and emphasizes the importance of technical skills in today's economy. It showcases successful examples of madrassas that have integrated technical education into their curriculum and highlights the stories of madrassa graduates who have gone on to become successful professionals. The article also discusses the challenges faced by madrassas in providing technical education and proposes possible solutions, such as partnerships with government agencies and NGOs, and the use of technology to deliver online education. In conclusion, the article emphasizes the significance of technical education in madrassas for both scholars and their communities. It calls upon stakeholders to support and invest in technical education programs in madrassas to empower scholars for livelihood and community development. By combining Islamic and technical education, madrassas can produce well-rounded individuals who are better equipped to navigate the modern world while staying true to their faith and values.